1993
DOI: 10.1095/biolreprod49.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Neonatal Exposure to Estrogens: A Suitable Tool for Reproductive Aging Studies in the Female Rat1

Abstract: The present study was designed to determine whether the modification of exposure time to large doses of estrogens provided a reliable model for early changes in reproductive aging. Silastic implants containing estradiol benzoate (EB) in solution were placed into 5-day-old female Wistar rats and removed 1 day (Ei1 group) or 5 days (Ei5) later. In addition, 100 micrograms [corrected] EB dissolved in 100 microliters corn oil was administered s.c. to another group (EI). Control rats received either vehicle implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In addition to its previously demonstrated effect on peripheral steroidogenic tissue (Rodriguez et al. 1993), we have now shown that the administration of β‐estradiol 3‐benzoate to female neonates induced pronounced decreases in the concentrations of progesterone and its metabolite allopregnanolone in the cerebral cortex that were apparent in both juvenile (3 weeks) and adult (2–6 months) animals.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…In addition to its previously demonstrated effect on peripheral steroidogenic tissue (Rodriguez et al. 1993), we have now shown that the administration of β‐estradiol 3‐benzoate to female neonates induced pronounced decreases in the concentrations of progesterone and its metabolite allopregnanolone in the cerebral cortex that were apparent in both juvenile (3 weeks) and adult (2–6 months) animals.…”
Section: Discussionsupporting
confidence: 50%
“…1993), we have now shown that the administration of β‐estradiol 3‐benzoate to female neonates induced pronounced decreases in the concentrations of progesterone and its metabolite allopregnanolone in the cerebral cortex that were apparent in both juvenile (3 weeks) and adult (2–6 months) animals. In contrast, the brain and plasma levels of 17β‐estradiol measured in adult rats were not affected by the neonatal administration of β‐estradiol 3‐benzoate, although a marked increase in estradiol plasma levels 24 h after injection of estradiol benzoate, that remained higher 10 days after injection has been previously observed (Rodriguez et al. 1993; Amateau et al.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The average lifetime of Wistar rats is about 30-31 months,52,53 and their puberty begins at 37-45 postnatal days 54-56. Therefore, the 8-week-old rats that were used in the present study were young animals.…”
Section: Discussionmentioning
confidence: 99%